2020
DOI: 10.1007/s11356-020-09864-0
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics modeling of multicomponent metal ions’ removal onto low-cost buckwheat hulls

Abstract: The process of adsorption from water solutions containing a ternary system of Cu (II), Zn (II), and Ni (II) ions onto buckwheat hulls as a biosorbent was considered. The sorption capacity for buckwheat hulls was determined in sorption equilibrium batch experiments. The sorption kinetics equation corresponding to the mechanism of metal ions with the adsorbent was assumed. A new method for modeling sorption in a packed column was presented. A system of partial differential equations describing the mass balance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…3. The Othmani et al (2020) Tomczak and Kaminski (2020). This study confirmed the fact that the ability of buckwheat hulls to remove heavy metal ions is in the following order: Cu (II) >> Ni (II) > Zn (II).…”
supporting
confidence: 80%
“…3. The Othmani et al (2020) Tomczak and Kaminski (2020). This study confirmed the fact that the ability of buckwheat hulls to remove heavy metal ions is in the following order: Cu (II) >> Ni (II) > Zn (II).…”
supporting
confidence: 80%
“…Recently, there has been increased interest in renewable by-products as promising raw materials that can be used in the production of a variety of food additives, chemicals, textiles, building materials, biotechnologies, and medicines because they are cheap and abundant agricultural bioproducts. The analytical characteristics of the buckwheat hemicelluloses show that they are a rich source of glucuronoxylan-type hemicelluloses (mainly composed of 4- o -methylglucuronoxylan) [ 8 , 9 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The model solution of each metal (lead, cadmium and manganese ions) was then mixed together in equal volume. In the multicomponent solution, the concentration of each of the cations in the mixture was the same[10,11]. The stock solution was diluted with distilled water to create the desired working solutions.…”
mentioning
confidence: 99%